MANDEVILLA CATIMBAUENSIS (APOCYNACEAE), A NEW SPECIES FROM THE SEMI-ARID REGION, PERNAMBUCO, BRAZIL - de Souza-Silva, R. F.; Rapini, A.; Morales, J. F. (Edinburgh Journal of Botany, 2010)
Mandevilla (Apocynaceae) is a neotropical genus which is well represented in Brazil. A recent taxonomic revision of the Brazilian species of Mandevilla subgenus Mandevilla included eight new species, one of them from the State of Pernambuco. Nevertheless, while preparing a survey of Apocynaceae from the Brazilian semi-arid region, a new species of the subgenus was recognised. Mandevilla catimbauensis Souza-Silva, Rapini & J.F.Morales is here described and illustrated. It is a twining plant with elliptic, glabrous leaves and hypocrateriform, purple flowers, known only from the Vale do Catimbau National Park, in the State of Pernambuco.
Keywords: Apocynoideae; caatinga; neotropics; Northeast Brazil; taxonomy